Nanofiber-based swab capable of collecting escherichia coli and detecting escherichia coli in situ and preparation of nanofiber-based swab

By adopting a nanofiber-based swab with dual network aerogel structure, the problem of low sample collection efficiency in bacterial detection and false negative results in the prior art is solved, high absorption and bacterial capture capabilities are achieved, and the detection process is simplified and detection sensitivity is improved.

CN119780426APending Publication Date: 2025-04-08DONGHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510105754.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art has problems in bacterial detection that sample collection efficiency is low, false negative test results are prone to false negatives, and the culture and identification process is time-consuming and requires professional operation.

Method used

Nanofiber-based swabs with dual network aerogel structure are used to form a porous structure through the overlap between the main nanofibers and modified sodium alginate nanofibers, and combined with the bonding network of silane sols, achieving high absorption and bacterial capture capabilities.

Benefits of technology

It improves bacterial collection efficiency and detection sensitivity, reduces false negative detection rate, simplifies the detection process, and quantitatively detects the concentration of E. coli within 30 minutes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005255373230000071
    Figure BDA0005255373230000071
  • Figure BDA0005255373230000072
    Figure BDA0005255373230000072
Patent Text Reader

Abstract

The invention relates to a nanofiber-based swab capable of collecting escherichia coli and detecting escherichia coli in situ and a preparation method thereof.The product is of a double-network aerogel structure and comprises a fiber skeleton network formed by mutual lap joint of main body nanofibers and a modified sodium alginate nanofiber network which is formed on the fiber skeleton network and has a bacterium capturing function; the diameter of the main body nanofiber is greater than that of the modified sodium alginate nanofiber; all the nanofibers are covalently connected through silane sol in the form of a Si-O-Si bonding network; the modified sodium alginate nanofiber is obtained by covalently linking recognition molecules to a sodium alginate macromolecular chain through amido bonds; the preparation method comprises the following steps: firstly, treating sodium alginate to obtain modified sodium alginate, then preparing a main body nanofiber membrane and a modified sodium alginate nanofiber membrane by adopting an electrostatic spinning method, and finally, treating to obtain the nanofiber-based swab. The preparation method is simple; the prepared product has high specific surface area, high absorptivity and high sensitivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bacteria detection and diagnosis instruments, and relates to a nanofiber-based swab capable of collecting and in-situ detecting Escherichia coli and a preparation method thereof. Background Art

[0002] Foodborne diseases, waterborne diseases and hospital-acquired infections caused by pathogenic bacteria are one of the major public health issues of common concern to the world. On average, one in 10 people worldwide becomes ill due to ingestion / infection with pathogenic bacteria each year. The major threat they pose to human survival lies not only in the virulence of the bacteria themselves and the dangers posed by the various toxins they produce, but also in the increasingly severe treatment situation for pathogenic bacteria due to the emergence of antibiotic resistance. In order to effectively prevent and control the spread of diseases, it is particularly important to conduct rapid, sensitive and accurate detection of pathogenic bacteria.

[0003] At present, the detection of pathogenic bacteria usually involves the collection of pathogen samples, including samples from food, water sources, and infection sites such as the oral cavity, wound surface, and urogenital tract, and then releasing the collected samples for subsequent morphological analysis, biochemical identification, immunological examination, etc. Since sample collection is mostly performed using a sampling swab, a disposable consumable consisting of a handheld plastic handle connected to a sampling head composed of a flocculating material formed by hydrophilic fibers. Limited by the structure, the microbial load of traditional sampling swabs is low, and 90% of the samples are trapped between the fibers, resulting in low release, resulting in false negative test results. However, the errors and mistakes introduced by specimen collection are only one of the difficulties faced by the existing technology. The culture and identification process after the isolation of pathogenic bacteria also has many shortcomings, which is time-consuming and complicated. The operation process is not suitable for on-site use and requires professional inspection personnel to operate. The immunological method used for auxiliary diagnosis has a relatively low detection sensitivity. When detecting antigens, it is easy to cross-react with similar antigens to produce false positives, and when detecting antibodies, false negatives are prone to occur due to the window period. Emerging molecular bioassay methods such as polymerase chain reaction technology have high specificity and require less sample, but in actual testing, the sample preparation process is complicated and requires professional nucleic acid amplification operation skills. These shortcomings limit their application in point-of-care (POC) testing and cannot be widely promoted, especially in resource-constrained settings.

[0004] Optical sensors have become an attractive and promising analytical method for rapid detection of bacteria because they do not require complex instruments and specialized operators. In particular, fluorescent sensors and colorimetric sensors can exhibit changes in fluorescence or color due to the presence of target analytes, which can be monitored directly by the naked eye.

[0005] Conventional swabs for bacterial detection involve releasing the collected samples and identifying them through plate culture, colony counting and other methods. It usually takes more than ten hours to obtain the test results, which is time-consuming and laborious. The new nanofiber-based swab developed by the existing technology is directly formed by winding the electrospun nanofiber membrane on a fixed axis in terms of structural design. On the other hand, it improves the detection sensitivity by improving its ability to absorb and release samples.

[0006] For example, Reference 1 (Development of PVA Electrospun Nanofibers for Fabrication of Bacteriological Swabs. Biology 2023, 12, 1404. https: / / doi.org / 10.3390 / biology12111404) uses an adhesive to wrap a PVA nanofiber membrane around a PS rod to make a nanofiber-based swab. Due to the high specific surface area of ​​the nanofiber, it exhibits absorption and release capabilities comparable to commercial foam swabs. Reference 2 (Ultra-absorptive Nanofiber Swabs for Improved Collection and Test Sensitivity of SARS-CoV-2 and other Biological Specimens. Nano Lett. 2021, 21, 3, 1508–1516) produces a nanofiber-based swab by expanding an electrospun membrane with gas foam around a fixed axis. Due to its hierarchical porous structure, it exhibits high absorption and release capabilities, which can improve detection sensitivity. However, none of them can avoid the subsequent complex and time-consuming culture and identification process.

[0007] Therefore, it is of great significance to study a nanofiber-based swab that can collect and detect Escherichia coli in situ and its preparation to solve the problems existing in the prior art. Summary of the invention

[0008] The purpose of the present invention is to solve the problems existing in the prior art and to provide a nanofiber-based swab capable of collecting and in-situ detecting Escherichia coli and its preparation method.

[0009] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0010] A nanofiber-based swab capable of collecting and in-situ detecting Escherichia coli, characterized in that: it is a double-network aerogel structure, including a fiber skeleton network formed by overlapping main nanofibers and a modified sodium alginate nanofiber network with bacteria capture function formed on the fiber skeleton network; the diameter of the main nanofiber is larger than that of the modified sodium alginate nanofiber; the main nanofiber has a thicker diameter and overlaps with each other to form a macroporous fiber skeleton, while the modified sodium alginate nanofiber has a thinner diameter and further forms a sheet-like fine network on the macroporous skeleton with a smaller pore size;

[0011] All nanofibers are covalently connected by silane sol with a Si-O-Si bonding network (i.e., the main nanofibers and the main nanofibers, the modified sodium alginate nanofibers and the modified sodium alginate nanofibers, and the main nanofibers and the modified sodium alginate nanofibers are all covalently connected by silane sol with a Si-O-Si bonding network), and the silane sol plays a role in stabilizing the bonding of the constructed fiber double network;

[0012] Modified sodium alginate nanofibers are obtained by covalently linking recognition molecules to sodium alginate macromolecular chains through amide bonds. For example, 3-aminophenylboronic acid groups can be covalently linked to the sodium alginate macromolecular chains. Phenylboronic acid will form reversible covalent bonds with diol groups on the surface of bacterial cells to achieve the effect of bacterial capture.

[0013] As the preferred technical solution:

[0014] As described above, the nanofiber-based swab capable of collecting and in-situ detecting Escherichia coli has a main nanofiber with a diameter of 200 to 350 nm and a modified sodium alginate nanofiber with a diameter of 50 to 150 nm.

[0015] As described above, a nanofiber-based swab that can collect and detect Escherichia coli in situ has high absorbency, and the absorption rate of the nanofiber-based swab is more than 1100% of the dry mass of the nanofiber-based swab. The nanofiber-based swab has high absorbency, and the absorption rate of the nanofiber-based swab is more than 1100% of the dry mass of the nanofiber-based swab. The nanofiber-based swab has high absorbency because it is a double-network aerogel structure with a three-dimensional porous network structure; the nanofiber-based swab has excellent bacteria capture ability, and the capture efficiency of Escherichia coli is more than 95%; the nanofiber-based swab has low release ability, and the release rate after capturing Escherichia coli is less than 10%. The nanofiber-based swab has low release ability because the bacteria collected by the nanofiber-based swab will be intercepted by the three-dimensional porous network structure and interact with the recognition molecules; wherein the capture efficiency of Escherichia coli refers to the ratio of the number of Escherichia coli captured from the sample by the nanofiber-based swab during the sample collection process to the total number of original Escherichia coli in the sample; and the release rate refers to the ratio of the number of Escherichia coli released from the nanofiber-based swab to the number of Escherichia coli captured in the nanofiber-based swab.

[0016] As described above, a nanofiber-based swab that can collect and detect Escherichia coli in situ has structural stability. After 10 compression cycles, the initial modulus, maximum compression stress and energy loss coefficient of the nanofiber-based swab are still maintained at more than 70% of the initial value.

[0017] A nanofiber-based swab capable of collecting and in-situ detecting Escherichia coli as described above, wherein the nanofiber-based swab is capable of detecting the concentration of Escherichia coli within 30 minutes;

[0018] The detection process is as follows: the nanofiber-based swab first collects the Escherichia coli sample, and then the nanofiber-based swab is immersed in a 0.5 mM isopropyl-β-d-thiogalactopyranoside (IPTG) solution and incubated at 37°C for 30 minutes to stimulate the expression of endogenous β-galactosidase (β-gal) in Escherichia coli; 100 μL of a 200 μg / mL 4-aminophenyl-β-D-galactopyranoside (PAPG) aqueous solution is added to the treated nanofiber-based swab, and reacted at 44°C for 30 minutes to completely decompose PAPG, and finally the nanofiber-based swab is reacted at 60°C for 30 minutes to produce color / fluorescence changes, and the concentration of Escherichia coli in the sample is quantitatively detected by quantifying the RGB value of the color change or fluorescence change.

[0019] The method for preparing a nanofiber-based swab capable of collecting and in-situ detecting Escherichia coli as described above comprises the following specific steps:

[0020] (1) Sodium alginate is dissolved in deionized water, activated with 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl), and then a recognition molecule is added, stirred at room temperature for 24 to 48 hours, dialyzed in deionized water for 3 to 7 days, and freeze-dried to obtain modified sodium alginate;

[0021] (2) preparing the main nanofiber membrane and modified sodium alginate nanofiber membrane by electrospinning method;

[0022] (3) Silane and water are uniformly mixed to form a silane solution, and then an acid catalyst is added to adjust the pH of the silane solution to 4 to 4.5, because the acidic environment can catalyze the hydrolysis reaction of silane, and then the pH-adjusted silane solution is magnetically stirred at room temperature for 30 to 60 minutes to ensure the hydrolysis of silane to obtain a silane sol;

[0023] (4) First, the modified sodium alginate nanofiber membrane obtained in step (2) is cut into pieces with a size of 0.5 cm × 0.5 cm to 1 cm × 1 cm and added to the silane sol obtained in step (3), and then the modified sodium alginate nanofiber membrane fragments are broken into single fibers I by a high-speed disperser and uniformly dispersed in the silane sol, and then the main nanofiber membrane obtained in step (2) is cut into pieces with a size of 0.5 cm × 0.5 cm to 1 cm × 1 cm and added to the silane sol dispersed with single fibers I, and then the main nanofiber membrane fragments are broken into single fibers II by a high-speed disperser, and the single fibers I are broken into single fibers III at the same time, to obtain a silane sol uniformly dispersed with single fibers II and single fibers III, i.e., a nanofiber dispersion; wherein the mass ratio of the main nanofiber membrane to the modified sodium alginate nanofiber membrane is 2 to 9:1; such operation can allow the modified sodium alginate nanofiber membrane to be treated for a longer time, so that the length of single fibers III is smaller than that of single fibers II;

[0024] (5) transferring the nanofiber dispersion obtained in step (4) into a 96-well plate, freezing it in a -20°C refrigerator, and then freeze-drying it in a freeze dryer for 12 to 24 hours to obtain a nanofiber-based swab;

[0025] The double network aerogel structure is formed during the freeze-drying process of step (5). During the freezing process of the dispersion, the temperature drops rapidly, and the solvent crystals nucleate and grow into ice crystals. The ice crystals continue to grow and squeeze out the two fibers (i.e., single fiber II and single fiber III), so that the nanofibers are aggregated between the ice crystals; the main nanofibers (single fiber II) with a thicker diameter are overlapped to form a fiber skeleton structure, while the modified sodium alginate nanofibers (single fiber III) have a thinner diameter and a shorter length. After being squeezed by the ice crystals, they are more likely to approach each other to form a secondary fine network structure.

[0026] As the preferred technical solution:

[0027] According to the preparation method described above, the silane is N-[3-(trimethoxysilyl)propyl]ethylenediamine (DAMO), dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride (DMOAP) or 3-(2-aminoethylamino)propylmethyldimethoxysilane (AAPTS); the mass fraction of the silane solution is 1% to 10%, and the acid catalyst is hydrochloric acid, sulfuric acid, acetic acid, oxalic acid, phosphoric acid, citric acid or nitric acid. In the silane cross-linking reaction, the acid can promote the cross-linking reaction of silane with water or other reactants; the recognition molecule is a molecule with an amino group and recognized and bound by Escherichia coli, and the amino group is to form an amide bond with the carboxyl group on the sodium alginate molecule to covalently connect the recognition molecule to the sodium alginate molecular chain, and the Escherichia coli recognition and binding means that the recognition molecule and Escherichia coli can be bound by chemical binding between functional groups, electrostatic binding or affinity binding between lectins and sugar molecules; the recognition molecule The nanofibers are phenylboronic acid derivatives (such as 3-aminophenylboronic acid), chitosan and its derivatives (such as chitosan), quaternary ammonium compounds (such as hexadecyltrimethylammonium chloride), thioamino compounds (such as 4-chlorophenylthioamino ester) or amino-containing glycoside compounds (such as 4-aminophenyl-α-D-pyranoside); through chemical bonding between functional groups, such as phenylboronic acid derivatives, in which the phenylboronic acid group forms a reversible covalent bond with the diol group on the surface of the Escherichia coli cell; through electrostatic force bonding, such as chitosan and its derivatives, the positively charged chitosan can form an electrostatic interaction force with the negatively charged Escherichia coli; through the affinity of lectins and sugar molecules, such as amino-containing glycoside compounds, in which mannose has an affinity with the FimH lectin of the Escherichia coli pili and can specifically bind; the sum of the mass fractions of single fiber II and single fiber III in the nanofiber dispersion is 0.5-2%.

[0028] According to the preparation method described above, the main nanofiber material is silicon dioxide, zinc oxide, aluminum oxide or cellulose; when the main nanofiber is an inorganic nanofiber, it is obtained by electrospinning to obtain inorganic / polymer hybrid nanofibers and then calcining at high temperature to remove the polymer component, and the polymer component is polyvinyl alcohol, polyvinyl butyral or polyvinyl pyrrolidone; the modified sodium alginate nanofiber membrane is first electrospinning the modified sodium alginate / water-soluble spinnable polymer blend, and then immersing the obtained nanofiber membrane in a 2-4wt% cross-linking agent aqueous solution; wherein the water-soluble spinnable polymer is polyethylene oxide or polyvinyl alcohol, and the cross-linking agent is calcium chloride, aluminum chloride, ferric chloride or zinc chloride.

[0029] In the preparation method as described above, the electrospinning process parameters of the main nanofiber membrane are: temperature 25±2°C, humidity 45±5%, spinning speed: 0.5~1.5mL / h, voltage 15~25kV, and receiving distance 15~20cm; the electrospinning process parameters of the modified sodium alginate nanofiber membrane are: temperature 30±2°C, humidity 35±5%, spinning speed 0.3~0.7mL / h, voltage 15~25kV, and receiving distance 15~20cm. The diameter of the modified sodium alginate nanofibers is controlled to be thinner by the spinning process parameters, and the diameter of the main nanofibers is thicker.

[0030] In the preparation method as described above, the rotation speed of the high-speed disperser is 10000-15000 rpm, and the single operation time is 10-30 min; the aspect ratios of the single fiber II and the single fiber III are both in the range of 100-400.

[0031] Principle of the invention:

[0032] The present invention discloses a nanofiber-based swab colorimetric / fluorescence dual-mode sensor capable of collecting and in-situ detecting Escherichia coli. PAPG can be hydrolyzed under the catalytic action of the specific enzyme β-gal produced by Escherichia coli to form p-aminophenol (PAP). PAP reacts with silane at 60°C for 30 minutes to form silicon nanoparticles (SiNPs) in-situ, producing visually visible color / fluorescence changes (the reason for the visually visible color / fluorescence changes is that the formed silicon nanoparticles themselves have color and fluorescence characteristics, which is attributed to the nanometer size of the silicon nanoparticles, which will produce optical dispersion phenomenon to produce color, and quantum confinement effect to produce fluorescence). The RGB value of the swab after reacting with bacterial liquid of different concentrations is read by software, and the data processing method is RGB value = R / G, a direct quantitative correlation between bacterial concentration and RGB value is established, and a standard relationship curve between RGB value and concentration of Escherichia coli suspension is obtained by linear fitting. Therefore, by measuring the RGB value of the nanofiber-based swab in actual detection, the concentration of Escherichia coli in the sample to be tested can be quantitatively determined by the standard curve.

[0033] The nanofiber-based swab of the present invention is a double-network aerogel structure. On the one hand, the porous structure formed by the fiber network has a capture and fixation effect on bacteria (captured by structural characteristics), and on the other hand, the modified sodium alginate nanofiber network plays a role in capturing bacteria through the interaction between recognition molecules and bacterial surface markers (adsorption achieved by chemical reaction between groups on the fiber surface and bacterial surface components), so during the sampling process, the nanofiber-based swab can collect more bacteria and fix them in the nanofiber-based swab, providing a good reaction place for bacteria and silane. Therefore, the nanofiber-based swab realizes the synergistic capture function of bacteria through the combination of the fiber network structure and modified sodium alginate and bacteria, thereby improving the detection sensitivity. At the same time, due to the covalent bond between the nanofiber network and the silane, it also plays a role in connecting the silane.

[0034] The nanofiber-based swab of the present invention can quickly collect samples and has high absorbency, low release rate, high bacterial capture ability and structural stability. Therefore, when the color / fluorescence change of the nanofiber-based swab is observed, it indicates that E. coli is present in the sample to be tested. By quantifying the RGB value of the color change or fluorescence change, the concentration of E. coli in the sample can also be quantitatively detected. For example, when wound exudate is tested, when the concentration of E. coli reaches greater than 10 5 CFU / mL, it means the wound is infected by E. coli.

[0035] Beneficial effects:

[0036] (1) The nanofiber-based swab of the present invention can collect and detect Escherichia coli in situ, and can detect Escherichia coli through a colorimetric / fluorescence dual-mode sensing system. The colorimetric / fluorescence dual-mode sensing system provides rich information and also has a built-in cross-reference self-correction and self-verification mechanism to avoid false positive outputs in environmental media, thereby providing more reliable and accurate detection results.

[0037] (2) Compared with other common types of swabs such as cotton swabs and flocked swabs, the nanofiber-based swab of the present invention can collect and detect Escherichia coli in situ. It has a nanofiber aerogel structure with high specific surface area and interconnected pores, which can improve the efficiency of sample collection and has a high bacterial load. It does not need to release samples and culture on plates, and can produce color / fluorescence changes in situ, which simplifies the detection process and greatly improves the detection sensitivity. The nanofiber-based swab can achieve qualitative detection of Escherichia coli by visually observing the changes in color / fluorescence within 30 minutes, and the bacterial concentration can be determined by measuring the RGB value of the nanofiber-based swab.

[0038] (3) The nanofiber-based swab of the present invention can collect and detect Escherichia coli in situ. The nanofiber-based swab has a large specific surface area and a porous structure, so it has high absorbency and can increase the load of pathogens during the collection process; and the nanofiber-based swab does not need to release pathogens for subsequent culture and identification, avoiding the problem of low release volume existing in current sampling swabs; therefore, it can effectively improve the detection sensitivity and reduce the false negative detection rate.

[0039] (4) The nanofiber-based swab of the present invention can collect and detect Escherichia coli in situ. The formation of color and fluorescence signals depends on silicon nanoparticles formed in situ rather than pre-synthesized nanoprobes. Therefore, the method does not require specific conditions and equipment, which greatly simplifies the detection / analysis process. At the same time, the higher extinction coefficient and superior fluorescence properties of silicon nanoparticles can greatly improve the sensitivity and responsiveness of the detection mode.

[0040] (5) The present invention provides a nanofiber-based swab that can collect and detect Escherichia coli in situ. The nanofiber-based swab achieves a synergistic capture function of bacteria through the fiber network structure and the combination of modified sodium alginate and bacteria, thereby improving the detection sensitivity. At the same time, the color signal RGB value of the nanofiber-based swab is read with the assistance of a smartphone, so that the quantitative detection effect of the bacterial concentration can be achieved quickly and conveniently.

[0041] (6) The present invention provides a method for preparing a nanofiber-based swab that can collect and detect Escherichia coli in situ, which realizes the synergistic capture function of bacteria through the fiber network structure and the combination of modified sodium alginate and bacteria, thereby improving the detection sensitivity; at the same time, due to the covalent bond between the nanofiber network and silane, it also plays the role of connecting silane. DETAILED DESCRIPTION

[0042] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0043] The test methods involved in the performance indicators in the embodiments and comparative examples of the present invention are as follows:

[0044] Absorption rate: First, record the weight of the nanofiber-based swab (W0), and then completely immerse the nanofiber-based swab in deionized water at 37°C for 30 minutes until saturation. After removing the surface moisture, record the saturated weight of the nanofiber-based swab (W1). The absorption rate is calculated according to the following formula:

[0045]

[0046] Capture efficiency of Escherichia coli: Stainless steel sheets (SS) were sterilized at 121°C for 15 minutes, and after the surface was dried and cooled to room temperature, 10 μL of 10 5 A suspension of E. coli at 100 CFU / mL was spotted on a sterilized stainless steel sheet and evenly spread on the surface using a sterile L-shaped coating rod. The inoculated surface was swab sampled with a nanofiber-based swab for 30 seconds, first wiping the entire sample from one side to the other in one direction, and then swabbing at 90° to the original direction. While wiping the surface, the swab was rotated while collecting the sample. The plate count method was used to quantify the number of bacteria remaining on the stainless steel sheet. The stainless steel sheet was placed in a petri dish and then covered with molten soft TSA (0.7% agar) containing 0.05 g / L rifampicin. After the soft TSA solidified, the plate was inverted and incubated at 37°C. The number of bacterial colonies on the agar plate was counted. After wiping the sample with the nanofiber-based swab, the swab was placed in 1 mL of release buffer, left to stand for 2 minutes, and then vigorously vortexed for 1 minute to release the bacterial cells captured in the swab. The number of released bacteria was counted using the plate count method. The bacterial capture efficiency (η) and release rate were calculated by the following formula:

[0047]

[0048] Among them, N int is the number of bacteria on the inoculated surface when not wiped, N coup is the number of bacteria remaining on the stainless steel sheet after wiping, N swab is the number of bacteria released from the nanofiber-based swab.

[0049] Compression cycle test: The compression performance of the nanofiber-based swab was tested using a universal testing machine with a disc fixture (Instron 3365, Instron, USA). The nanofiber-based swab samples were all cylinders with a diameter of 15 mm and a height of 10 mm. The compression strain was set to 50% and the compression rate was 300% min -1 To test the sample's 10-cycle compression performance, the configured pressure sensor has a sensitivity of 100N.

[0050] Example 1

[0051] A method for preparing a nanofiber-based swab capable of collecting and in-situ detecting Escherichia coli, the specific steps are as follows:

[0052] (1) dissolving sodium alginate in deionized water to obtain a sodium alginate solution with a concentration of 10 mg / mL, activating the solution with 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, adding 3-aminophenylboronic acid, stirring the solution at room temperature for 24 hours, dialyzing the solution in deionized water for 3 days, and freeze-drying the solution to obtain modified sodium alginate;

[0053] The molar ratio of sodium alginate to 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is 1:1, and the molar ratio of sodium alginate to 3-aminophenylboronic acid is 2:1;

[0054] (2) electrospinning a mixture of modified sodium alginate and polyethylene oxide (manufacturer: Aladdin, molecular weight: 1000 kDa), and then immersing the obtained nanofiber membrane in a 2 wt % calcium chloride aqueous solution to obtain a modified sodium alginate nanofiber membrane with an average diameter of 50 nm;

[0055] The electrospinning process parameters were: temperature 30 °C, humidity 35%, spinning speed 0.3 mL / h, voltage 15 kV, and receiving distance 15 cm;

[0056] (3) The main nanofibers made of silica and polyvinyl butyral (manufacturer: Aladdin, molecular weight: 40,000-70,000 Da) were co-electrospun, and then the polymer components were removed by high-temperature calcination to obtain a main nanofiber membrane with an average diameter of 200 nm;

[0057] The electrospinning process parameters of the main nanofibers were: temperature 25 °C, humidity 45%, spinning speed: 0.5 mL / h, voltage 15 kV, receiving distance 15 cm;

[0058] (4) uniformly mixing N-[3-(trimethoxysilyl)propyl]ethylenediamine and water to form a silane solution with a mass fraction of 1%, then adding hydrochloric acid to adjust the pH of the silane solution to 4, and then magnetically stirring the pH-adjusted silane solution at room temperature for 30 minutes to obtain a silane sol;

[0059] (5) First, the modified sodium alginate nanofiber membrane obtained in step (2) is cut into pieces with a size of 0.5 cm×0.5 cm and added to the silane sol obtained in step (4), and then the modified sodium alginate nanofiber membrane fragments are broken into single fibers I by a high-speed disperser and uniformly dispersed in the silane sol, and then the main nanofiber membrane obtained in step (3) is cut into pieces with a size of 0.5 cm×0.5 cm and added to the silane sol dispersed with single fibers I, and then the main nanofiber membrane fragments are broken into single fibers II by a high-speed disperser, and the single fibers I are broken into single fibers III at the same time, to obtain a silane sol uniformly dispersed with single fibers II and single fibers III, i.e., a nanofiber dispersion;

[0060] The speed of the high-speed disperser is 10000 rpm, and the single operation time is 30 min. The mass ratio of the main nanofiber membrane and the modified sodium alginate nanofiber membrane is 9:1. The sum of the mass fractions of single fiber II and single fiber III in the nanofiber dispersion is 0.5%. The aspect ratio of single fiber II is 100, and the aspect ratio of single fiber III is 100.

[0061] (6) The nanofiber dispersion obtained in step (5) was transferred to a 96-well plate, placed in a -20°C refrigerator to freeze, and then placed in a freeze dryer for freeze drying for 12 hours to obtain a nanofiber-based swab.

[0062] The final nanofiber-based swab that can collect and detect Escherichia coli in situ is a double-network aerogel structure, including a fiber skeleton network formed by overlapping main nanofibers and a modified sodium alginate nanofiber network with bacteria capture function formed on the fiber skeleton network; all nanofibers are covalently connected by silane sol with a Si-O-Si bonding network; the absorption rate of the nanofiber-based swab is 1700% of the dry mass of the nanofiber-based swab; the capture efficiency of the nanofiber-based swab for Escherichia coli is 95.5%, and the release rate after capturing Escherichia coli is 9%; after 10 compression cycles, the initial modulus of the nanofiber-based swab remains at 75% of the initial value, the maximum compression stress remains at 75% of the initial value, and the energy loss coefficient remains at 73% of the initial value; the nanofiber-based swab can detect the concentration of Escherichia coli within 30 minutes.

[0063] Comparative Example 1

[0064] A method for preparing a nanofiber-based swab is basically the same as Example 1, except that the operations of steps (1) and (2) are omitted, that is, the nanofiber dispersion in step (5) only includes single fibers II broken from the main nanofiber network.

[0065] The nanofiber-based swab had a capture efficiency of 50% for E. coli.

[0066] By comparing Comparative Example 1 with Example 1, it can be found that the capture efficiency of the nanofiber-based swab for Escherichia coli is reduced. This is because there is no recognition and fixation effect of the modified sodium alginate fiber on the bacteria. The capture of bacteria by the nanofiber-based swab only relies on the porous structure formed by the fiber network, so the capture efficiency of Escherichia coli is low.

[0067] Comparative Example 2

[0068] A method for preparing a nanofiber-based swab is basically the same as that of Example 1, except that the operation of step (3) is omitted, that is, the nanofiber dispersion of step (5) only includes single fibers I broken down from modified sodium alginate nanofibers.

[0069] After 10 compression cycles, the initial modulus of the nanofiber-based swab remained at 50% of the initial value, the maximum compressive stress remained at 50% of the initial value, and the energy loss coefficient remained at 50% of the initial value.

[0070] By comparing Comparative Example 2 with Example 1, it can be found that the cyclic compression performance of the nanofiber-based swab is reduced. This is because the modified sodium alginate nanofibers are smaller in diameter and shorter in length than the main nanofibers, and the formed fiber skeleton structure is thinner and fragile, which is easily damaged during the cyclic compression process.

[0071] Example 2

[0072] A method for preparing a nanofiber-based swab capable of collecting and in-situ detecting Escherichia coli, the specific steps are as follows:

[0073] (1) Sodium alginate was dissolved in deionized water to obtain a sodium alginate solution with a concentration of 10 mg / mL, and chitosan (manufacturer: McLean, molecular weight: 100 kDa) was added after activation with 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, and the solution was stirred at room temperature for 36 h, and then dialyzed in deionized water for 4 days, and freeze-dried to obtain modified sodium alginate;

[0074] The molar ratio of sodium alginate to 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is 1:1, and the molar ratio of sodium alginate to chitosan is 2:1;

[0075] (2) electrospinning modified sodium alginate and polyvinyl alcohol (manufacturer: Aladdin, brand: 1788), and then immersing the obtained nanofiber membrane in a 3 wt % aluminum chloride aqueous solution to obtain a modified sodium alginate nanofiber membrane with an average diameter of 75 nm;

[0076] The electrospinning process parameters were: temperature 28 °C, humidity 40%, spinning speed 0.4 mL / h, voltage 18 kV, and receiving distance 16 cm;

[0077] (3) The main nanofibers made of zinc oxide and polyvinyl alcohol (manufacturer: Aladdin, brand: 1788) were co-electrospinned, and then the polymer components were removed by high-temperature calcination to obtain a main nanofiber membrane with an average diameter of 250 nm;

[0078] The electrospinning process parameters of the main nanofibers were: temperature 23 °C, humidity 50%, spinning speed: 0.8 mL / h, voltage 18 kV, receiving distance 16 cm;

[0079] (4) uniformly mixing dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and water to form a silane solution with a mass fraction of 2%, then adding sulfuric acid to adjust the pH of the silane solution to 4.1, and then magnetically stirring the pH-adjusted silane solution at room temperature for 35 minutes to obtain a silane sol;

[0080] (5) First, the modified sodium alginate nanofiber membrane obtained in step (2) is cut into pieces with a size of 0.6 cm×0.6 cm and added to the silane sol obtained in step (4), and then the modified sodium alginate nanofiber membrane fragments are broken into single fibers I by a high-speed disperser and uniformly dispersed in the silane sol, and then the main nanofiber membrane obtained in step (3) is cut into pieces with a size of 0.6 cm×0.6 cm and added to the silane sol dispersed with single fibers I, and then the main nanofiber membrane fragments are broken into single fibers II by a high-speed disperser, and the single fibers I are broken into single fibers III at the same time, to obtain a silane sol uniformly dispersed with single fibers II and single fibers III, i.e., a nanofiber dispersion;

[0081] The speed of the high-speed disperser is 11000rpm, and the single operation time is 28min. The mass ratio of the main nanofiber membrane and the modified sodium alginate nanofiber membrane is 7:1. The sum of the mass fractions of single fiber II and single fiber III in the nanofiber dispersion is 0.8%. The aspect ratio of single fiber II is 150, and the aspect ratio of single fiber III is 150.

[0082] (6) The nanofiber dispersion obtained in step (5) was transferred to a 96-well plate, placed in a -20°C refrigerator to freeze, and then placed in a freeze dryer for freeze drying for 14 hours to obtain a nanofiber-based swab.

[0083] The final nanofiber-based swab that can collect and detect Escherichia coli in situ has a double-network aerogel structure, including a fiber skeleton network formed by overlapping main nanofibers and a modified sodium alginate nanofiber network with bacteria capture function formed on the fiber skeleton network; all nanofibers are covalently connected to each other through a Si-O-Si bonding network via silane sol; the absorption rate of the nanofiber-based swab is 1600% of the dry mass of the nanofiber-based swab; the capture efficiency of the nanofiber-based swab for Escherichia coli is 96%, and the release rate after capturing Escherichia coli is 8%; after 10 compression cycles, the initial modulus of the nanofiber-based swab remains at 80% of the initial value, the maximum compression stress remains at 80% of the initial value, and the energy loss coefficient remains at 76% of the initial value; the nanofiber-based swab can detect the concentration of Escherichia coli within 30 minutes.

[0084] Example 3

[0085] A method for preparing a nanofiber-based swab capable of collecting and in-situ detecting Escherichia coli, the specific steps are as follows:

[0086] (1) dissolving sodium alginate in deionized water to obtain a sodium alginate solution with a concentration of 10 mg / mL, activating the solution with 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, adding 4-aminophenyl-α-D-pyranoside, stirring at room temperature for 48 hours, dialyzing the solution in deionized water for 5 days, and freeze-drying the solution to obtain modified sodium alginate;

[0087] The molar ratio of sodium alginate to 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is 1:1, and the molar ratio of sodium alginate to 4-aminophenyl-α-D-mannopyranoside is 2:1;

[0088] (2) electrospinning a mixture of modified sodium alginate and polyethylene oxide (manufacturer: Aladdin, molecular weight: 1000 kDa), and then immersing the obtained nanofiber membrane in a 4 wt % ferric chloride aqueous solution to obtain a modified sodium alginate nanofiber membrane with an average diameter of 100 nm;

[0089] The electrospinning process parameters were: temperature 29 °C, humidity 38%, spinning speed 0.5 mL / h, voltage 20 kV, and receiving distance 17 cm;

[0090] (3) The main nanofibers made of aluminum oxide and polyvinyl pyrrolidone (manufacturer: Sinopharm, molecular weight: 40,000 Da) were co-blended by electrospinning, and then the polymer components were removed by high-temperature calcination to obtain a main nanofiber membrane with an average diameter of 275 nm;

[0091] The electrospinning process parameters of the main nanofibers were: temperature 24 °C, humidity 48%, spinning speed: 1 mL / h, voltage 20 kV, receiving distance 17 cm;

[0092] (4) 3-(2-aminoethylamino)propylmethyldimethoxysilane and water were uniformly mixed to form a silane solution with a mass fraction of 4%, and then acetic acid was added to adjust the pH of the silane solution to 4.2, and then the pH-adjusted silane solution was magnetically stirred at room temperature for 40 minutes to obtain a silane sol;

[0093] (5) First, the modified sodium alginate nanofiber membrane obtained in step (2) is cut into pieces with a size of 0.7 cm×0.7 cm and added to the silane sol obtained in step (4), and then the modified sodium alginate nanofiber membrane fragments are broken into single fibers I by a high-speed disperser and uniformly dispersed in the silane sol, and then the main nanofiber membrane obtained in step (3) is cut into pieces with a size of 0.7 cm×0.7 cm and added to the silane sol dispersed with single fibers I, and then the main nanofiber membrane fragments are broken into single fibers II by a high-speed disperser, and the single fibers I are broken into single fibers III at the same time, to obtain a silane sol uniformly dispersed with single fibers II and single fibers III, i.e., a nanofiber dispersion;

[0094] The speed of the high-speed disperser is 12000 rpm, and the single operation time is 25 min. The mass ratio of the main nanofiber membrane and the modified sodium alginate nanofiber membrane is 6:1. The sum of the mass fractions of single fiber II and single fiber III in the nanofiber dispersion is 1%. The aspect ratio of single fiber II is 200, and the aspect ratio of single fiber III is 200.

[0095] (6) The nanofiber dispersion obtained in step (5) was transferred to a 96-well plate, placed in a -20°C refrigerator to freeze, and then placed in a freeze dryer for freeze drying for 16 hours to obtain a nanofiber-based swab.

[0096] The final nanofiber-based swab that can collect and detect Escherichia coli in situ has a double-network aerogel structure, including a fiber skeleton network formed by overlapping main nanofibers and a modified sodium alginate nanofiber network with bacteria capture function formed on the fiber skeleton network; all nanofibers are covalently connected by silane sol with a Si-O-Si bonding network; the absorption rate of the nanofiber-based swab is 1500% of the dry mass of the nanofiber-based swab; the capture efficiency of the nanofiber-based swab for Escherichia coli is 96.5%, and the release rate after capturing Escherichia coli is 7%; after 10 compression cycles, the initial modulus of the nanofiber-based swab remains at 85% of the initial value, the maximum compression stress remains at 85% of the initial value, and the energy loss coefficient remains at 79% of the initial value; the nanofiber-based swab can detect the concentration of Escherichia coli within 30 minutes.

[0097] Example 4

[0098] A method for preparing a nanofiber-based swab capable of collecting and in-situ detecting Escherichia coli, the specific steps are as follows:

[0099] (1) dissolving sodium alginate in deionized water to obtain a sodium alginate solution with a concentration of 10 mg / mL, activating the solution with 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, adding hexadecyltrimethylammonium chloride, stirring the solution at room temperature for 24 hours, dialyzing the solution in deionized water for 6 days, and freeze-drying the solution to obtain modified sodium alginate;

[0100] The molar ratio of sodium alginate to 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is 1:1, and the molar ratio of sodium alginate to hexadecyltrimethylammonium chloride is 2:1.

[0101] (2) electrospinning modified sodium alginate and polyvinyl alcohol (manufacturer: Aladdin, brand: 1788), and then immersing the obtained nanofiber membrane in a 2 wt % zinc chloride aqueous solution to obtain a modified sodium alginate nanofiber membrane with an average diameter of 125 nm;

[0102] The electrospinning process parameters were: temperature 30 °C, humidity 34%, spinning speed 0.6 mL / h, voltage 22 kV, and receiving distance 19 cm;

[0103] (3) Cellulose was directly dissolved in the ionic liquid 1-allyl-3-methylimidazole chloride (AMIMCl), and then electrospinning was used to prepare a main nanofiber membrane with an average diameter of 300 nm;

[0104] The electrospinning process parameters were: temperature 25 °C, humidity 46%, spinning speed: 1.2 mL / h, voltage 22 kV, receiving distance 18 cm;

[0105] (4) uniformly mixing N-[3-(trimethoxysilyl)propyl]ethylenediamine and water to form a silane solution with a mass fraction of 6%, then adding oxalic acid to adjust the pH of the silane solution to 4.3, and then magnetically stirring the pH-adjusted silane solution at room temperature for 45 minutes to obtain a silane sol;

[0106] (5) First, the modified sodium alginate nanofiber membrane obtained in step (2) is cut into pieces with a size of 0.8 cm×0.8 cm and added to the silane sol obtained in step (4), and then the modified sodium alginate nanofiber membrane fragments are broken into single fibers I by a high-speed disperser and uniformly dispersed in the silane sol, and then the main nanofiber membrane obtained in step (3) is cut into pieces with a size of 0.8 cm×0.8 cm and added to the silane sol dispersed with single fibers I, and then the main nanofiber membrane fragments are broken into single fibers II by a high-speed disperser, and the single fibers I are broken into single fibers III at the same time, to obtain a silane sol uniformly dispersed with single fibers II and single fibers III, i.e., a nanofiber dispersion;

[0107] The speed of the high-speed disperser is 13000 rpm, and the single operation time is 20 min. The mass ratio of the main nanofiber membrane and the modified sodium alginate nanofiber membrane is 5:1. The sum of the mass fractions of single fiber II and single fiber III in the nanofiber dispersion is 1.3%. The aspect ratio of single fiber II is 300, and the aspect ratio of single fiber III is 300.

[0108] (6) The nanofiber dispersion obtained in step (5) was transferred to a 96-well plate, placed in a -20°C refrigerator to freeze, and then placed in a freeze dryer for freeze drying for 18 hours to obtain a nanofiber-based swab.

[0109] The final nanofiber-based swab that can collect and detect Escherichia coli in situ has a double-network aerogel structure, including a fiber skeleton network formed by overlapping main nanofibers and a modified sodium alginate nanofiber network with bacteria capture function formed on the fiber skeleton network; all nanofibers are covalently connected by silane sol with a Si-O-Si bonding network; the absorption rate of the nanofiber-based swab is 1400% of the dry mass of the nanofiber-based swab; the capture efficiency of the nanofiber-based swab for Escherichia coli is 97%, and the release rate after capturing Escherichia coli is 6%; after 10 compression cycles, the initial modulus of the nanofiber-based swab remains at 90% of the initial value, the maximum compression stress remains at 90% of the initial value, and the energy loss coefficient remains at 82% of the initial value; the nanofiber-based swab can detect the concentration of Escherichia coli within 30 minutes.

[0110] Example 5

[0111] A method for preparing a nanofiber-based swab capable of collecting and in-situ detecting Escherichia coli, the specific steps are as follows:

[0112] (1) dissolving sodium alginate in deionized water to obtain a sodium alginate solution with a concentration of 10 mg / mL, activating the solution with 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, adding 4-chlorophenylthiamine, stirring the solution at room temperature for 36 hours, dialyzing the solution in deionized water for 7 days, and freeze-drying the solution to obtain modified sodium alginate;

[0113] Wherein, the molar ratio of sodium alginate to 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is 1:1, and the molar ratio of sodium alginate to 4-chlorophenylthiamine ester is 2:1;

[0114] (2) electrospinning a mixture of modified sodium alginate and polyethylene oxide (manufacturer: Aladdin, molecular weight: 1000 kDa), and then immersing the obtained nanofiber membrane in a 3 wt % calcium chloride aqueous solution to obtain a modified sodium alginate nanofiber membrane with an average diameter of 150 nm;

[0115] The electrospinning process parameters were: temperature 31 °C, humidity 32%, spinning speed 0.7 mL / h, voltage 25 kV, and receiving distance 20 cm;

[0116] (3) The main nanofibers made of silica and polyvinyl alcohol (manufacturer: Aladdin, brand: 1788) were electrospun by blending, and then the polymer components were removed by high-temperature calcination to obtain a main nanofiber membrane with an average diameter of 325 nm;

[0117] The electrospinning process parameters of the main nanofibers were: temperature 26 °C, humidity 42%, spinning speed: 1.4 mL / h, voltage 24 kV, receiving distance 19 cm;

[0118] (4) uniformly mixing dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and water to form a silane solution with a mass fraction of 8%, then adding phosphoric acid to adjust the pH of the silane solution to 4.5, and then magnetically stirring the pH-adjusted silane solution at room temperature for 50 minutes to obtain a silane sol;

[0119] (5) First, the modified sodium alginate nanofiber membrane obtained in step (2) is cut into pieces with a size of 0.9 cm×0.9 cm and added to the silane sol obtained in step (4), and then the modified sodium alginate nanofiber membrane fragments are broken into single fibers I by a high-speed disperser and uniformly dispersed in the silane sol, and then the main nanofiber membrane obtained in step (3) is cut into pieces with a size of 0.9 cm×0.9 cm and added to the silane sol dispersed with single fibers I, and then the main nanofiber membrane fragments are broken into single fibers II by a high-speed disperser, and the single fibers I are broken into single fibers III at the same time, to obtain a silane sol uniformly dispersed with single fibers II and single fibers III, i.e., a nanofiber dispersion;

[0120] The speed of the high-speed disperser is 14000 rpm, and the single operation time is 15 min. The mass ratio of the main nanofiber membrane and the modified sodium alginate nanofiber membrane is 4:1. The sum of the mass fractions of single fiber II and single fiber III in the nanofiber dispersion is 1.7%. The aspect ratio of single fiber II is 350, and the aspect ratio of single fiber III is 350.

[0121] (6) The nanofiber dispersion obtained in step (5) was transferred to a 96-well plate, placed in a -20°C refrigerator to freeze, and then placed in a freeze dryer for freeze drying for 20 hours to obtain a nanofiber-based swab.

[0122] The final nanofiber-based swab that can collect and detect Escherichia coli in situ is a double-network aerogel structure, including a fiber skeleton network formed by overlapping main nanofibers and a modified sodium alginate nanofiber network with bacteria capture function formed on the fiber skeleton network; all nanofibers are covalently connected by silane sol with a Si-O-Si bonding network; the absorption rate of the nanofiber-based swab is 1300% of the dry mass of the nanofiber-based swab; the capture efficiency of the nanofiber-based swab for Escherichia coli is 98%, and the release rate after capturing Escherichia coli is 5%; after 10 compression cycles, the initial modulus of the nanofiber-based swab remains at 93% of the initial value, the maximum compression stress remains at 93% of the initial value, and the energy loss coefficient remains at 85% of the initial value; the nanofiber-based swab can detect the concentration of Escherichia coli within 30 minutes.

[0123] Example 6

[0124] A method for preparing a nanofiber-based swab capable of collecting and in-situ detecting Escherichia coli, the specific steps are as follows:

[0125] (1) dissolving sodium alginate in deionized water to obtain a sodium alginate solution with a concentration of 10 mg / mL, activating the solution with 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, adding 3-aminophenylboronic acid, stirring the solution at room temperature for 48 hours, dialyzing the solution in deionized water for 7 days, and freeze-drying the solution to obtain modified sodium alginate;

[0126] The molar ratio of sodium alginate to 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is 1:1, and the molar ratio of sodium alginate to 3-aminophenylboronic acid is 2:1;

[0127] (2) electrospinning modified sodium alginate and polyvinyl alcohol (manufacturer: Aladdin, brand: 1788), and then immersing the obtained nanofiber membrane in a 4 wt % aluminum chloride aqueous solution to obtain a modified sodium alginate nanofiber membrane with an average diameter of 150 nm;

[0128] The electrospinning process parameters were: temperature 32 °C, humidity 30%, spinning speed 0.5 mL / h, voltage 21 kV, and receiving distance 18 cm;

[0129] (3) The main nanofibers made of zinc oxide and polyvinyl pyrrolidone (manufacturer: Sinopharm, molecular weight: 40,000 Da) were co-electrospinned, and then the polymer components were removed by high-temperature calcination to obtain a main nanofiber membrane with an average diameter of 350 nm;

[0130] The electrospinning process parameters of the main nanofibers were: temperature 27 °C, humidity 40%, spinning speed: 1.5 mL / h, voltage 25 kV, receiving distance 20 cm;

[0131] (4) 3-(2-aminoethylamino)propylmethyldimethoxysilane and water were uniformly mixed to form a silane solution with a mass fraction of 10%, and then citric acid was added to adjust the pH of the silane solution to 4.5, and then the pH-adjusted silane solution was magnetically stirred at room temperature for 60 minutes to obtain a silane sol;

[0132] (5) First, the modified sodium alginate nanofiber membrane obtained in step (2) is cut into pieces with a size of 1 cm×1 cm and added to the silane sol obtained in step (4), and then the modified sodium alginate nanofiber membrane fragments are broken into single fibers I by a high-speed disperser and uniformly dispersed in the silane sol, and then the main nanofiber membrane obtained in step (3) is cut into pieces with a size of 1 cm×1 cm and added to the silane sol dispersed with single fibers I, and then the main nanofiber membrane fragments are broken into single fibers II by a high-speed disperser, and the single fibers I are broken into single fibers III at the same time, to obtain a silane sol uniformly dispersed with single fibers II and single fibers III, i.e., a nanofiber dispersion;

[0133] The speed of the high-speed disperser is 15000 rpm, and the single operation time is 10 min; the mass ratio of the main nanofiber membrane and the modified sodium alginate nanofiber membrane is 2:1; the sum of the mass fractions of single fiber II and single fiber III in the nanofiber dispersion is 2%; the aspect ratio of single fiber II is 400, and the aspect ratio of single fiber III is 400;

[0134] (6) The nanofiber dispersion obtained in step (5) was transferred to a 96-well plate, placed in a -20°C refrigerator to freeze, and then placed in a freeze dryer for freeze drying for 24 hours to obtain a nanofiber-based swab.

[0135] The final nanofiber-based swab that can collect and detect Escherichia coli in situ is a double-network aerogel structure, including a fiber skeleton network formed by overlapping main nanofibers and a modified sodium alginate nanofiber network with bacteria capture function formed on the fiber skeleton network; all nanofibers are covalently connected by silane sol with a Si-O-Si bonding network; the absorption rate of the nanofiber-based swab is 1200% of the dry mass of the nanofiber-based swab; the capture efficiency of the nanofiber-based swab for Escherichia coli is 99%, and the release rate after capturing Escherichia coli is 4%; after 10 compression cycles, the initial modulus of the nanofiber-based swab remains at 95% of the initial value, the maximum compression stress remains at 95% of the initial value, and the energy loss coefficient remains at 88% of the initial value; the nanofiber-based swab can detect the concentration of Escherichia coli within 30 minutes.

Claims

1. A nanofiber-based swab for collecting and in-situ detecting Escherichia coli, characterized in that: It is a double-network aerogel structure, including a fiber skeleton network formed by overlapping main nanofibers and a modified sodium alginate nanofiber network with bacteria capture function formed on the fiber skeleton network; The diameter of the main nanofibers is larger than that of the modified sodium alginate nanofibers; All nanofibers are covalently connected by silane sol with a Si-O-Si bonding network; The modified sodium alginate nanofibers are obtained by covalently linking the recognition molecules to the sodium alginate macromolecular chains through amide bonds.

2. A nanofiber-based swab for collecting and in-situ detecting Escherichia coli according to claim 1, characterized in that: The diameter of the main nanofiber is 200-350nm, and the diameter of the modified sodium alginate nanofiber is 50-150nm.

3. A nanofiber-based swab for collecting and in-situ detecting Escherichia coli according to claim 1, characterized in that: The absorption rate of the nanofiber-based swab is more than 1100% of the dry mass of the nanofiber-based swab, the capture efficiency of the nanofiber-based swab for Escherichia coli is more than 95%, and the release rate of the nanofiber-based swab after capturing Escherichia coli is less than 10%.

4. A nanofiber-based swab for collecting and in-situ detecting Escherichia coli according to claim 3, characterized in that: After 10 compression cycles, the initial modulus, maximum compressive stress, and energy loss coefficient of the nanofiber-based swabs all remained above 70% of their initial values.

5. A nanofiber-based swab for collecting and in-situ detecting Escherichia coli according to claim 4, characterized in that: The nanofiber-based swab was able to detect the concentration of E. coli within 30 minutes.

6. A method for preparing a nanofiber-based swab for collecting and in-situ detecting Escherichia coli according to any one of claims 1 to 5, characterized in that The specific steps are as follows: (1) dissolving sodium alginate in deionized water, activating it with 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, adding a recognition molecule, stirring at room temperature for 24 to 48 hours, then dialyzing it in deionized water for 3 to 7 days, and freeze-drying it to obtain modified sodium alginate; (2) preparing the main nanofiber membrane and modified sodium alginate nanofiber membrane by electrospinning method; (3) uniformly mixing silane and water to form a silane solution, then adding an acid catalyst to adjust the pH of the silane solution to 4 to 4.5, and then magnetically stirring the pH-adjusted silane solution at room temperature for 30 to 60 minutes to obtain a silane sol; (4) First, the modified sodium alginate nanofiber membrane obtained in step (2) is cut into pieces with a size of 0.5 cm×0.5 cm to 1 cm×1 cm and added to the silane sol obtained in step (3), and then the modified sodium alginate nanofiber membrane fragments are broken into single fibers I by a high-speed disperser and uniformly dispersed in the silane sol, and then the main nanofiber membrane obtained in step (2) is cut into pieces with a size of 0.5 cm×0.5 cm to 1 cm×1 cm and added to the silane sol dispersed with single fibers I, and then the main nanofiber membrane fragments are broken into single fibers II by a high-speed disperser, and the single fibers I are broken into single fibers III at the same time, to obtain a silane sol uniformly dispersed with single fibers II and single fibers III, i.e., a nanofiber dispersion; wherein the mass ratio of the main nanofiber membrane to the modified sodium alginate nanofiber membrane is 2 to 9:1; (5) The nanofiber dispersion obtained in step (4) is transferred to a 96-well plate and freeze-dried for 12 to 24 hours to obtain a nanofiber-based swab.

7. The preparation method according to claim 6, characterized in that: The silane is N-[3-(trimethoxysilyl)propyl]ethylenediamine, dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride or 3-(2-aminoethylamino)propylmethyldimethoxysilane; the mass fraction of the silane solution is 1% to 10%, the acid catalyst is hydrochloric acid, sulfuric acid, acetic acid, oxalic acid, phosphoric acid, citric acid or nitric acid; the recognition molecule is a phenylboronic acid derivative, chitosan and its derivatives, quaternary ammonium compounds, thioamino compounds or amino-containing glycoside compounds; the sum of the mass fractions of single fiber II and single fiber III in the nanofiber dispersion is 0.5 to 2%.

8. The preparation method according to claim 6, characterized in that: The main nanofiber material is silicon dioxide, zinc oxide, aluminum oxide or cellulose.

9. The preparation method according to claim 8, characterized in that: The electrospinning process parameters of the main nanofiber membrane are: temperature 25±2℃, humidity 45±5%, spinning speed: 0.5~1.5mL / h, voltage 15~25kV, and receiving distance 15~20cm; the electrospinning process parameters of the modified sodium alginate nanofiber membrane are: temperature 30±2℃, humidity 35±5%, spinning speed 0.3~0.7mL / h, voltage 15~25kV, and receiving distance 15~20cm.

10. The preparation method according to claim 6, characterized in that: The rotation speed of the high-speed disperser is 10000-15000 rpm, and the single operation time is 10-30 minutes; the aspect ratios of the single fiber II and the single fiber III are both in the range of 100-400.